ANALISIS FAKTOR YANG MEMPENGARUHI PRODUKSI TEBU PADA SUB SEKTOR PERKEBUNAN DI PROVINSI JAWA TIMUR TAHUN 2011-2015 - Moch. Arif Dausin Nazula Achadin (Jurnal Ekonomi Pembangunan, 2017)
The goal of this research is to know the influence of the land area and the amount of sugar cane plantation labor in the plantation in East Java province year 2011-2015 and analysis whether there is a difference between production of Kabupaten/Kota cane producer on a plantation in East Java province year 2011-2015. Analysis tool used is a panel data regression then do hypothesis testing with F-test, t-test, and the coefficient of Determination () on error rate α = 5%.The results of the regression analysis of the data panel with the selected model is a Random Effect Model showed that the land area of influential labor and significantly to the amount of production value of each 0.97 to land area and 0.04 for amount of labor. While the value of the coefficient of determination () is 0.99 or 99%, this indicates that the ability of the variable land area and the amount of labor in explaining the amount of production of 99%.